1998
DOI: 10.1097/00043764-199809000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Psychological Distress, Social Functioning, and Coping Style in Treated and Untreated Patients With Solvent-Induced Chronic Toxic Encephalopathy

Abstract: Patients with organic solvent-induced toxic encephalopathy (TE) (n = 13) were followed up seven years after the application of an intervention program. They were also compared with untreated TE patients diagnosed at the same time (n = 26) and with unexposed referents (n = 39). Psychological distress, social function, and coping ability and style were measured with the Symptom Checklist-90, Interview Schedule of Social Interaction, and Sense of Coherence and Strategies to Handle Stress questionnaires. Both TE g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…After a more detailed review eight more articles were excluded because they appeared not to be treatment outcome studies or did not evaluate psychological treatment methods. Three studies were identified as follow-up studies of already selected studies [18, 19, 20]. A PsychLIT search revealed an additional 73 articles, 12 of which met inclusion criteria and were included for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a more detailed review eight more articles were excluded because they appeared not to be treatment outcome studies or did not evaluate psychological treatment methods. Three studies were identified as follow-up studies of already selected studies [18, 19, 20]. A PsychLIT search revealed an additional 73 articles, 12 of which met inclusion criteria and were included for further evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…The articles of Abjornsson et al [11] and Lindgren et al [10] were based on the same study group. In 1998, Abjornsson et al [19]presented 7-year follow-up results of their study. Eight studies provided quality D evidence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disabilities arising from the moderate to severe dysfunctions in memory and attention frequently persist after the exposure to solvents has ended, compromising daily functioning, social and occupational participation and quality of life (Baker, 1994, Abjornsson et al, 1998. Also, patients with CSE show a higher prevalence of both mood and anxiety disorders according to DSM IV criteria as compared with a community sample (Visser et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However only a few follow-up descriptions of neuropsychological effects exist in this field. In three studies patients with previously diagnosed chronic solvent intoxications were examined [6][7][8] . Williamson and Winder investigated workers at the beginning of their work with solvents and again after one and two years 9) .…”
Section: Introductionmentioning
confidence: 99%